Introduction to engineering - (:unkn) unknown (Wydawnictwo Politechniki Łódzkiej, 2008)
Lately, the technology development takes place at a great rate, which requires from each of us a continuous observation of this process. In order to understand the latest achievements of technology, it is necessary to know the basic concepts, phenomena and technological processes. We know also that in the majority of businesses beside the issues concerning the economic sciences like organization or management, the problems of technology are very important. This book has been prepared, first of all, for students of the first years of managerial specializations. The program of study at the Faculty of Management and Organization, at the Technical University of Lodz, effectively combines the issues of organization and management with the technical disciplines and practices. Specific subjects allow students to understand the technological aspects of selected industries, as well as the production management, organization, marketing management and the problems of management in the information society. Many times, the students who start the studies in the fields of Management or Management and Production Engineering, are graduates of economic high schools without the basic knowledge concerning physics and other technical issues. This book is the selection of a few issues concerning the area of technology, associated with the activities of teaching and research of Division of Fundamental Technical Research and Industrial Ecology of the Faculty of Management and Organization at the Technical University of Lodz. The very wide range of problems related to the technique, forced authors to choose only the most important concepts, definitions and problems. It is difficult to discuss, even in general, all the major issues concerning the introduction to the technology. This book is also a support material and a base for studying other subjects, including the specialization' technical subjects. This book can be used by students of other departments of technical universities, by students of postgraduate studies and by managers in industry. In time of globalization and international students exchange, the English language is very often used in science and technology, so it requires a basic knowledge of vocabulary.
Dla studentów zarządzania produkcją i innych studiów technicznych.
Scientific Editor of the Division : Lewandowski, Jerzy
Keywords: mechanika stosowana; wytrzymałość materiałów; technologia budowy maszyn; produkcja - planowanie; technologia - aspekt środowiskowy; applied mechanics; strength of materials; machine construction technology; production - planning; technology - environmental aspect